Character education analysis through school culture in elementary schools - Yulia, Rahmi; Hidayati, Abna; Miaz, Yalvema; Muhammadi (Indonesian Research Journal in Education |IRJE|, 2025)
This research aims to describe the implementation of character education through school culture, along with supporting and inhibiting factors, in Public elementary school 13 Lubuk Alung, Ampek Nagari District. The research is qualitative with descriptive and inductive analysis. Data collection techniques include observation, interviews, and documentary studies. The results indicate that the implementation of character education through school culture at Public elementary school 13 Lubuk Alung is through four developmental areas: habituation, programmed activities, interest and talent development, and exemplary behavior. The outcomes of implementing character education are shaping students who are faithful and devoted to the One Almighty God, possess noble character, embrace global diversity, are independent, cooperative, creative, and have critical thinking skills. In addition, this research concludes that implementing character education occurs continuously and, often unconsciously, positively impacts students' character. The results of the implementation of character education strengthening through school culture at Public elementary school 13 Lubuk Alung have a positive impact on the formation of students' characters by the Pancasila student profile, including: (a) students become individuals who are faithful and devoted to the One Almighty God and have noble morals; (b) students have a character of global diversity; (c) students can be independent; (d) students have a cooperative character; (e) students become creative individuals; and (f) students also have critical thinking skills.